Anti-Inflammatory Effects of TRAF-Interacting Protein in Rheumatoid Arthritis Fibroblast-Like Synoviocytes - Qing-Zhu Kong; Li-Tao Guo; Jia-Ning Yang; Yan-Fei Wang; Jing-Xin Zhao; Su-Hong Kong; Meng Zhang; Shi Yan; Yu Jin (Mediators of Inflammation)
Rheumatoid arthritis (RA) is a chronic systemic inflammatory disease characterized by inflammatory cell infiltration, synovial inflammation, and cartilage destruction. Proliferative fibroblast-like synoviocytes (FLS) play crucial roles in both propagation of inflammation and joint damage because of their production of great amount of proinflammatory cytokines and proteolytic enzymes. In this study, we investigate the role of TRAF-interacting protein (TRIP) in regulating inflammatory process in RA-FLS. TRIP expression was attenuated in RA-FLS compared with osteoarthritis- (OA-) FLS. Overexpression of TRIP significantly inhibited the activation of NF-κB signaling and decreased the production of proinflammatory cytokines and matrix metalloproteinases (MMPs) in TNFα-stimulated RA-FLS. Furthermore, TRIP was found to interact with transforming growth factor β-activated kinase 1 (TAK1) and promoting K48-linked polyubiquitination of TAK1 in RA-FLS. Our results demonstrate that TRIP has anti-inflammatory effects on RA-FLS and suggest TRIP as a potential therapeutic target for human RA.